Cultural & Family Values & Promoting National Identity in the Context of Globalization - Chebita, Ali (Milev Journal of Research and Studies, 2019)
The family is the first nucleus in which the individual grows and his personality is formed and his ideas are adopted and his orientations are made, through impregnation of the various cultural values ​​and patterns adopted by society for the sake of cohesion and continuity and progress and leadership and security, using different mechanisms and means that make the individual and the family maintain the values ​​that distinguish society and then maintain On its security and stability, and for each stage of life, methods and methodologies used by the family to achieve the above, as they and until recently had patterns, functions and mechanisms in achieving social and cultural formation that enabled them to enhance their security internally and externally, but the changes that occur in Patterns of family formation and its role in light of the changes taking place as a result of the cultural, knowledge, media and technological globalization that affected the fundamental roles and changed their social and cultural structures, which necessitates relying on fortifying their cultural structure and trying to restore the value fragility (religious, cultural, ethical, social) that it afflicted As a result of the strong flow of global cultural values ​​and their influence on various aspects, starting from this characterization of the current cultural values ​​in the family, its role and importance in promoting the national identity and its destinies, we call us through this research paper to investigate and research what What is the effectiveness of affirming the cultural values ​​of the family in our society in order to enhance our national identity by securing it religiously, morally and culturally, in light of the globalization's dominance and its control over various aspects of life? How are the various implications of globalization reflected on the cultural identity of the young?